Understanding challenges as they impact on hospital-level care for pre-eclampsia in rural Ethiopia: a qualitative study - Andrew Shennan; Charlotte Hanlon; Jane Sandall; Rosie Mayston; Tanya Robbins; Tigist Eshetu Guangul; Rahel Demissew; Ahmed Abdella (BMJ Open, 2023)
Objective To explore hospital-level care for pre-eclampsia in Ethiopia, considering the perspectives of those affected and healthcare providers, in order to understand barriers and facilitators to early detection, care escalation and appropriate management.Setting A primary and a general hospital in southern Ethiopia.Participants Women with lived experience of pre-eclampsia care in the hospital, families of women deceased due to pre-eclampsia, midwives, doctors, integrated emergency surgical officers and healthcare managers.Results This study identified numerous systemic barriers to provision of quality, person-centred care for pre-eclampsia in hospitals. Individual staff efforts to respond to maternal emergencies were undermined by a lack of consistency in availability of resources and support. The ways in which policies were applied exacerbated inequities in care. Staff improvised as a means of managing with limited material or human resources and knowledge. Social hierarchies and punitive cultures challenged adequacy of communication with women, documentation of care given and supportive environments for quality improvement.Conclusions Quality care for pre-eclampsia requires organisational change to create a safe space for learning and improvement, alongside efforts to offer patient-centred care and ensure providers are equipped with knowledge, resources and support to adhere to evidence-based practice.